Fastening and assembly [ - Cook, Jerome T.; Green, Richard G. (Dearborn, Michigan : Society of Manufacturing Processes, 2001)
Examines a range of mechanical fastener types and assembly devices, explains adhesive bonding, and demonstrates various manual and automated assembly systems
1. Integral fasteners -- 2. Threaded fasteners -- 3. Non-threaded fasteners -- 4. Stapling
Producer / Director / Cameraman, Jerome T. Cook ; Written, Richard G. Green
System requirements: DVD drive
In English
Keywords: Adhesives; Fasteners; Instructional films / Nonfiction films